South African nuclear art: a first reflection - Jo-Ansie van Wyk (Cogent Arts & Humanities)
Nuclear art is a developed and recognised artistic practice. The study conceptualises nuclear art and presents a first exploration of South African nuclear art; albeit a small corpus. exists, Drawing from an analytical framework derived from international literature on nuclear art, the study shows that South African nuclear art is not insular. Several themes occur, namely the nuclear bomb attacks on Hiroshima and Nagasaki in 1945, the link between gender, patriarchy and nuclear energy, the presence of global nuclear iconography, and the juxtaposition of the violence and destruction of nuclear energy with the spectacular and the nuclear sublime. South African nuclear art is not insular but reference to apartheid South Africa’s own nuclear weapons are absent. No South African nuclear art for the period 1970 to 1989, the heyday of the apartheid nuclear weapons programme, could have been found to include in this first take of South African nuclear art. South African artists’ nuclear works display unique and innovative artistic practices and are predominantly produced by white female South Africans. This either reflects white privilege and/or (wilful or not) ignorance of prevailing nuclear colonialism in South Africa and elsewhere.